Mecanismos envolvidos na tolerância à dessecação em sementes e plântulas de Tabebuia aurea (Silva Manso) Benth. & Hook.f. ex S. Moore (Bignoniaceae) - Santos, Cristianne Santana (2019)
The desiccation tolerance in seeds and seedlings is an important aspect for the use of species in the ecological regeneration, mainly of the Dry Tropical Forests. Therefore, in the present work, the limits, physiological aspects and the relationship of the discontinuous hydration in the desiccation tolerance (TD) in Tabebuia aurea seeds and seedlings were analyzed. Firstly, the degree of TD of the seeds and the response of the slow and rapid desiccation in different water contents (0, 0.75, 1.5, 2.25 and 3%) of the freshly collected seeds water were analyzed, besides the influence of the discontinuous hydration in TD of T. aurea seeds that were submitted to 0, 1, 2 and 3 cycles of hydration and dehydration (HD cycles) in three hydration times (½ of the time of the first soaking phase and ¼ and ¾ of the second stage of imbibition). Already during the development, the ability of the seedlings to tolerate desiccation in three different radicle sizes (0 to 2, 2 to 5 and 5 to 10 mm) was evaluated. In addition, it was also carried out the quantification of reducing sugars and total proteins in all evaluated treatments. The seeds and seedlings of T. aurea showed a high TD, in the two types of desiccation evaluated, being observed an increase in the content of reducing sugars with the decrease of the water content in the seeds, as well as a reduction of the content of these sugars in the seedlings. Discontinuous hydration did not promote TD increase of the seeds of the species studied. However, when they passed HD cycles, an increase in the protein content was observed in the seeds submitted to rapid desiccation. It can be concluded that the high TD presented by the seeds and seedlings of T. aurea with radicles up to 10 mm is related to the alterations in the biochemical mechanisms important in the maintenance of this tolerance and that can be promoted by the discontinuous hydration.